2005
DOI: 10.1080/014850190959081
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Sperm Quality Analyzer-v (Sqa-V) for the Assessment of Sperm Quality in Infertile Men

Abstract: & The aim of this study was to evaluate the correlation of new of Sperm Quality Analyzer (SQA-V) with the computer-assisted sperm analysis (CASA) and manual semen analysis estimates. One hundred five fresh semen samples were analyzed using SQA-V and CASA and manual semen analysis. Significant correlations of sperm concentration (p < 0.0001), sperm motility (p < 0.0001), and normal morphology (p < 0.0001) were observed between SQA-V variables and manual semen analysis estimates. There also were significant corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our study shows that sperm concentration results obtained by the SQA-V are in agreement with manual results, and our findings are similar to those reported earlier by Akashi et al (24) and Fuse et al (25). We found no significant linear deviation when quantifying the agreement between the two methods.…”
Section: Discussionsupporting
confidence: 94%
“…Our study shows that sperm concentration results obtained by the SQA-V are in agreement with manual results, and our findings are similar to those reported earlier by Akashi et al (24) and Fuse et al (25). We found no significant linear deviation when quantifying the agreement between the two methods.…”
Section: Discussionsupporting
confidence: 94%
“…These systems are pre-calibrated vs. manual analysis with strict conformity to WHO 5th Edition and follow regular quality control protocols [9]. Several studies have demonstrated that automated sperm analyzers could provide an accurate and highly correlated alternative to manual sperm analysis [9][10][11][12][13][14][15][16][17]. Basically, there are two categories of automated sperm analyzers on the market which can be characterized by their detection technology.…”
Section: Introductionmentioning
confidence: 99%
“…The SQA-V GOLD is a fully automated system, which is based on the detection of electro-optical signals generated by moving spermatozoa and interpreted by proprietary algorithms. This signal processing for sperm motility is coupled with spectrophotometry technology to determine sperm concentration [9,12,15]. The Computer Assisted Sperm Analysis (CASA) systems are based on another principle: capturing microscopic images and image processing to detect motile and immotile spermatozoa through acquisition of rapid and successive frames [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different CASA systems use different mathematical algorithms to calculate various sperm quality parameters, leading to the greatest disadvantage in the clinical application of CASA, with unreliability of comparative parameters across all devices (Akashi, Mizuno, Okumura, & Fuse, 2005;Amann & Waberski, 2014;Dearing, Kilburn, & Lindsay, 2014;Kanakasabapathy et al, 2017;Lammers, Splingart, Barriere, Jean, & Freour, 2014). Moreover, different CASA systems use different mathematical algorithms to calculate various sperm quality parameters, leading to the greatest disadvantage in the clinical application of CASA, with unreliability of comparative parameters across all devices (Akashi, Mizuno, Okumura, & Fuse, 2005;Amann & Waberski, 2014;Dearing, Kilburn, & Lindsay, 2014;Kanakasabapathy et al, 2017;Lammers, Splingart, Barriere, Jean, & Freour, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most CASA systems allow partial automation in routine sperm analysis, but they have also shown limited success due to poor accuracy at low and high sperm counts and the high cost of virtually all CASA devices. Moreover, different CASA systems use different mathematical algorithms to calculate various sperm quality parameters, leading to the greatest disadvantage in the clinical application of CASA, with unreliability of comparative parameters across all devices (Akashi, Mizuno, Okumura, & Fuse, 2005;Amann & Waberski, 2014;Dearing, Kilburn, & Lindsay, 2014;Kanakasabapathy et al, 2017;Lammers, Splingart, Barriere, Jean, & Freour, 2014). Although CASA provides quantitative data on sperm kinetics, most CASA systems still rely greatly on highly trained technicians and require an additional bulky component for data collection and computational units for data analysis.…”
mentioning
confidence: 99%